Report of the Committee on Utilisation of External Assistance - Planning Commission (Planning Commission, 1964)
The Committee on Utilisation o£ External Assistance was constituted by a Resolution of the Government of India in the Ministry of Finance, Department of Economic Affairs (No. F. 12/35/63 EF Co-ord. dated the 19th June, 1963). the circumstances leading to the appointment of the Committee are described in the Resolution as follows: — “With the growing momentum of development and the diversification of the economy, there has been a significant increase in the range and scale of foreign aid operations in the country in recent years. the expeditious and effective utilisation of available external assistance has become an important factor in accelerating the pace of development.
Finance, Department of Economic Affairs Government of India